Potential Applications of Halloysite Nanotubes as Drug Carriers: A Review. (20th April 2022) - Ganapathy, Dhanraj; Shanmugam, Rajeshkumar; Pitchiah, Sivaperumal; Murugan, Preethika; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Durairaj, Kaliannan; Sundramoorthy, Ashok K.
Abstract : Halloysite nanotubes (HNTs) are naturally occurring tubular clay nanomaterials that are made from multiple-rolled aluminosilicate kaolin panels. The aluminol and siloxane groups on the surface of HNT facilitate the formation of hydrogen bonds with biomaterials on its surface. It is a cost-effective nanomaterial that found applications in a variety of fields of science and technology. The biocompatible properties of HNT resulted in various applications such as in nanomedicine, biomedicine, tissue engineering, drug delivery, sequence delivery, cancer, stem cells isolation, bioimaging, and sensors. Due to its tubular form, it has played a vital role as drug delivery carriers, superior nanocarrier for numerous medicines, and biological agents with larger loading capacity and longer releasing kinetics. HNT has also been investigated and used extensively in targeted drug transfer applications with a variety of medicines. These studies provided positive outcomes which have led to versatile medicinal applications. Herein, we have highlighted the latest developments on HNT-based drug carriers.